Impact Of Indonesian Islamic Bank To Build Growth Premium Income Of Shari’a Insurance Company In Indonesia Market - Ronaldo, Reza; Meilia, Maya; Alaaraj, Hasan (Universitas Islam Negeri Raden Intan Lampung, 2018)
In 2017 the Indonesian Islamic Bank contributes premium income to Shari’a Insurance in Indonesia amounting to 1.8 billion rupiah. There are 5 (five) Islamic Banks in Indonesia that contribute premiums to national Shari’a Insurance. The big five Islamic Banks in Indonesia are; Bank Mandiri Shari’a (BMS), Bank Muamalat Indonesia (BMI), Bank Negara Indonesia Shari’a (BNIS), Bank Rakyat Indonesia Shari’a (BRIS) and Bank Mega Shari’a. With increasing income of the National Shari’a Bank, it is expected to have an increasingly income of Shari’a National. Indonesian Islamic Banks give significant contribution to the growth of Shari’a Insurance premiums in Indonesia. While other Shari’a financial instruments in Indonesia such as Shari’a BPR, Leasing Shari’a are not so large, so they have not provided significant premium contributions to National Shari’a Insurance. If other Islamic Financial Instruments can accelerate market share, then of course it will be able to provide additional premiums that are not small to Shari’a Insurance in Indonesia. This research is expected to be further developed in order to increase the income of Islamic banks in Indonesia while at the same time growing national Shari’a Insurance Premium Income. Keywords : Islamic Bank, Sharia Insurance and Takaful.